Seroepidemiological study of Toxoplasma gondii in equines in Northern Egypt - Elmahallawy, Ehab Kotb; Hassan, Marwa F.; Cano-Terriza, David; Albalawi, Nada Oudah; Fajardo, Tomás; Gouda, Asmaa Aboelabbas; Atiba, Ayman; Hendawy, Ahmed; Villena, Isabelle; Barakat, Ashraf Mohamed; Alzaylaee, Hind; Almería, Sonia; et al. (Frontiers in Veterinary Science, 2025)
IntroductionToxoplasmosis, caused by the intracellular protozoan Toxoplasma gondii (T. gondii), continues to be a widespread parasitic zoonotic disease globally. The seroepidemiology of T. gondii infection in Egyptian equids, particularly donkeys, remains insufficiently explored. The present study was designed to assess the seroprevalence of T. gondii in equines from Northern Egypt.MethodsA total of 360 serum samples from two equine species (157 horses and 203 donkeys) were obtained during 2023. The Modified Agglutination Test (MAT, cut-off of 1:25) was used to screen for the anti-T. gondii antibodies. The study also analyzed potential risk factors that could contribute to the exposure of the animals to the parasite, including species, breed, sex, age, and the specific location of each animal.ResultsThe overall seroprevalence of T. gondii among examined equines was 41.11% (95% Confidence Interval [CI]: 36.03–46.19). The relationships between seropositivity and explanatory variables were analyzed using a Generalized Estimating Equation (GEE) approach. The seroprevalence of T. gondii was significantly higher in donkeys (51.23%) than in horses (28.03%; p < 0.001; odds ratio [OR] = 2.99; 95% CI: 2.35–3.81).ConclusionsCollectively, our findings revealed a high T. gondii exposure among equine species in Northern Egypt, with a notably higher seroprevalence in donkeys compared to horses. This study represents one of the most extensive serosurveys of T. gondii in equids conducted in Egypt, featuring the largest sample size of donkeys examined to date. It also examined previously unexplored risk factors related to parasite exposure in equids. The present findings highlight the critical importance of performing periodical surveillance, monitoring, and management of the parasite among equids, which might have a major impact on animal and public health.